Pakan Ruminansia Ramah Lingkungan Menggunakan Karbohidrat Fermentable - SM Salamony; FM Suhartati; M Bata (AGRICOLA, 2019)
This study aims to examine the use of fermentable carbohydrates in rice straw ammonia as an environmentally friendly ruminant feed and digestibility in the rumen in vitro. The experiment was carried out using 1000 g of dry material of rice straw, 2% fermentable carbohydrates, 4% urea, and 10% water. The balance of fermentable carbohydrates in ammoniated rice straw with a concentrate of 40: 60 and divided into four treatments, that is R0: rice straw without fermentable carbohydrates, R1: onggok, R2: cassava, R3: bran and R4 waste vermicelli with five replications. Data were analyzed using honesty significant different. The results showed that the highest digestibility of dry matter was found in group R3 (44.8013%) and the lowest in the R4 group (41.9795%). The highest digestibility of organic matter was in the R3 group (47.4450%) and the lowest in the R4 group (43.1665%). Based on the results of the study that the increase in KcBK, KcBO feed was far better than the R4 group. The use of fermentable carbohydrates increases KcBK and KcBO in the rumen. From the results of the study it can be concluded that the amoniation of rice straw added to the feed additive does not interfere with rumen fermentation activity in vitro.